Radiographic Outcome Analysis Following A Modified Lapidus with Fusion of the First Intermetatarsal and First Intercuneiform Joints. Issue 4 (16th October 2019) - Long, Joseph; Lauf, Jason; Al-Issa, Mohammed; Whitehead, Brent; Cheney, Nicholas; Law, Timothy; Schimmoeller, Kaitlyn
Category: Bunion Introduction/Purpose: The Lapidus procedure is becoming more popular in the surgical correction of hallux valgus deformities. Bunion correction surgeries in general demonstrate good patient outcomes, however the recurrence rates are variable and are a concern for patient morbidity. The senior author of this study performs a modified Lapidus procedure where the first intermetatarsal, and first intercuneiform joints are fused along with the standard fusion of the first tarsometatarsal joint. We believe that this fusion will address the recurrence rate associated with the Lapidus procedure. Our theory is that recurrence occurs at the normally unfused intermetatarsal and intercuneiform joints, and when these joints are fused recurrence will be unable to occur. Methods: We reviewed the charts of patients who underwent the modified Lapidus procedure between 2014 and 2017 performed by the senior author. This review yielded 47 cases, of which 34 met the study criteria as a primary bunion repair with a preoperative X-ray, a postoperative X-ray at first surgical follow up, and a final postoperative X-ray =90 days postoperatively. Of the 13 charts that did not qualify, 11 had inadequate follow up data/radiographs, and 2 cases were revisions. The 34 remaining cases were then analyzed for IMA, HVA, and evidence of fusion on X-ray. Two patient subsets were created for additional analysis of the first and last postoperative X-rays with no patient overlap. 19 cases created subgroup A as they contained patients whose last postoperative X-rays were weight bearing. 6 cases were analyzed as subgroup B having final postoperative X-rays that were non-weight bearing. All first postoperative X-rays were non-weight bearing. Results: The average time of radiographic follow up was 10.5±8.9 months (range 3.1-41.5). There was evidence of fusion failure at the IMT joint in 7 cases (21%), and these patients were removed from group data analysis. Another case was excluded due to the great toe falling into varus. In the remaining 26 cases, the difference in IMA and HVA was significant between the last preoperative and first postoperative X-ray (p<0.001; p<0.001), but not significant between the first and final postoperative X-rays (p=0.26; p=0.77). Subgroups A and B did not see statistically significant changes in IMA (p=0.40; p=0.19) or HVA (p=0.78; p=0.34) measurements between the first and last postoperative X-rays. Of note, the cases with IMT fusion failure saw a statistically significant increase in IMA measurements (p=0.001). Conclusion: Our study results suggest that the modified Lapidus procedure has good results in the short term, maintaining the operative reduction at a mean follow up time of 10 months. Our hypothesis that the intermetatarsal and intercuneiform joint fusion prevents bunion recurrence is supported by the fused cases showing no significant differences after at least 90 days postoperatively, while the unfused cases showed significant changes to their IMA angles after at least 90 days postoperatively. Although the study population is small, our data suggests that this procedure can maintain the correction achieved in surgery.